2020
DOI: 10.1017/s027226311900069x
|View full text |Cite
|
Sign up to set email alerts
|

Schematic Diagrams in Second Language Learning of English Prepositions

Abstract: In the current study of applied cognitive linguistics (CL), schematic diagrams that represent generalizations of physical-spatial experience were applied in a computer-based tutor that trained English prepositions for second language (L2) learners. Behavioral and electrophysiological (ERP) measures were used to examine whether schematic-diagram feedback provided by the tutor had an instructional advantage over the minimally informed correctness feedback. Behavioral results confirmed this prediction and further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
(77 reference statements)
1
5
0
Order By: Relevance
“…The notion of image schema has frequently been applied to L2 pedagogy (Wong, Zhao, & MacWhinney, 2018; Kissling, Tyler, Warren, & Negrete, 2018; Tyler, 2012; Tyler et al., 2011). Recently, Zhao, Huang, Zhou, and Wang (2020) confirmed the neurocognitive advantages of using schematic diagram instruction for the acquisition of English prepositions. That said, it is important to note that schematic diagrams are not simply visual aids to provide additional contextual information.…”
Section: Theoretical Backgroundmentioning
confidence: 95%
“…The notion of image schema has frequently been applied to L2 pedagogy (Wong, Zhao, & MacWhinney, 2018; Kissling, Tyler, Warren, & Negrete, 2018; Tyler, 2012; Tyler et al., 2011). Recently, Zhao, Huang, Zhou, and Wang (2020) confirmed the neurocognitive advantages of using schematic diagram instruction for the acquisition of English prepositions. That said, it is important to note that schematic diagrams are not simply visual aids to provide additional contextual information.…”
Section: Theoretical Backgroundmentioning
confidence: 95%
“…Recently, diagrams have become increasingly prevalent in CL-inspired L2 pedagogy for teaching abstract concepts, grammar and vocabulary (Wong et al, 2018;Zhao et al, 2020). It was believed that diagrams assist learners in establishing conceptual mappings between physical and non-physical domains of human experience, encouraging deep processing and dual coding of language and images to enhance the mnemonic benefits for learning outcomes (Boers et al, 2008).…”
Section: The Application Of Schematic Diagramsmentioning
confidence: 99%
“…Despite the abundance of diagrams in the CL literature, the present study focused on over and in as target prepositions. These diagrams have previously demonstrated efficacy as L2 instructional aids in classroom settings (Wong et al, 2018;Zhao et al, 2020), making them intriguing candidates for further exploration of their psychological underpinnings. To investigate the extent to which L2 learners' mental imagery patterns resemble those of NSs, we have collected data from adult English NSs to establish a baseline.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty of acquiring prepositions when learning a new language is also addressed in cognitive studies. Lowie and Verspoor (2004) offered a cognitive discussion of the progression of preposition acquisition in Dutch learners of English; Hung et al (2018) found a cognitive approach that focuses on both spatial and metaphorical meanings to be effective for teaching English prepositions; and Tyler (2012); Bratož (2014); Wong et al (2018); Zhao et al (2020) all advocate for a cognitively driven approach to teaching prepositions as well. Pedagogical approaches for teaching English prepositions are also compared in Mueller (2011Mueller ( , 2012.…”
Section: Prepositions Are Uniquely Challenging For Learnersmentioning
confidence: 99%